Analysis of the Influence of Organizational Culture, Competence, and Employee Welfare on Organizational Citizenship Behavior at Company: Analisis Pengaruh Budaya Organisasi Kompetensi Dan Kesejahteraan Karyawan Terhadap Organizational Citizenship Behavior di Perusahaan - Susetyo, Izzuel Harits; Sumartik (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of the study was to analyze the influence of organizational culture . competence and employe welfare on organizational citizenship behavior (OCB) partially or simultaneosly at PT. Ekadharma international Tbk. in this study the researrcher used Quantitative research. The data in this study used tabulated data from respondents trough both observation and the questionnaire results. The sampling technique was purposive sampling. The sample used in this study were sixty employees at PT. Ekadharma Internasional Tbk. The analysis used multiple linear regression analysis, t test, F test and classical assumption test using SPSS version 25 software. The results of thisstudy indicated that : (1) Organizational Culture, Competence and welfare partially affected organizational citizenship behavior (OCB), (2) Organizational Culture, Competence, and Welfare simultaneously affected organizational citizenship behavior (OCB). based on the finding results, the researcher concluded that competencevariable had the most significant effect on Organizational Citizenship Behavior (OCB) at PT. Ekadharma Internasional Tbk.